Two new species of Endelus Deyrolle, 1864 (Coleoptera, Buprestidae) from China with notes on Endelus acutiplicis Obenberger, 1944 - Kalashian, Mark (Zootaxa, 2025)
Two species of the genus Endelus from China, E. (Endelus) storozhenkoi sp. nov. from Guangdong Province and E. (E.) jiangxiensis sp. nov. from Jiangxi Province, are described, illustrated and compared with related species from E. (E.) collinus species group. Endelus (E.) acutiplicis Obenberger, 1944 is newly placed in the same group, and a lectotype of the species is designated.